Educating the next generation of psychiatrists in the use of clinical neuromodulation therapies: what should all psychiatry residents know? - Menon, Sahit N.; Torrico, Tyler; Luber, Bruce; Gindoff, Brian; Cullins, Lisa; Regenold, William; Lisanby, Sarah H. (Frontiers in Psychiatry, 2024)
A variety of neuromodulation treatments are available today and more are on the way, but are tomorrow's psychiatrists prepared to incorporate these tools into their patients' care plans? This article addresses the need for training in clinical neuromodulation for general psychiatry trainees. To ensure patient access to neuromodulation treatments, we believe that general psychiatrists should receive adequate education in a spectrum of neuromodulation modalities to identify potential candidates and integrate neuromodulation into their multidisciplinary care plans. We propose curricular development across the four FDA-cleared modalities currently available in psychiatric practice: electroconvulsive therapy (ECT), transcranial magnetic stimulation (TMS), deep brain stimulation (DBS), and vagus nerve stimulation (VNS). With a focus on psychiatry residency training, the article delineates core learning components for each neuromodulation technique. For each modality, we review the clinical training status, the respective FDA-cleared indications, mechanisms of action, clinical indications and contraindications, adverse effects, informed consent process, dosing considerations, and clinical management guidelines. The approach outlined in this article aims to contribute to the development of a well-rounded generation of psychiatry trainees with the capacity to navigate the growing field of neuromodulation. Whether or not a psychiatrist specializes in delivering neuromodulation therapies themselves, it is incumbent on all psychiatrists to be able to identify patients who should be referred to neuromodulation therapies, and to provide comprehensive patient care before, during and after clinical neuromodulation interventions to optimize outcomes and prevent relapse.